O merchandising e sua influência nas compras planejadas em supermercados - Bueno, Laury de Almeida (2006)
Since the self-service system introduction in the retail, one more important influence has been added to the consumer s purchase decision process: the store atmospherics. Elements like store s layout, its illumination, odors, noises, number of people buying, signaling and even more specific aspects, such as temperature and air quality, have been considered nowadays for both retail and environmental psychology experts as basic factors and strong influences on the consumer purchase behavior. On the other hand, the huge easiness offered by auto-attendance selling system had greatly reduced the necessity of planning purchases in supermarkets the more representative type of store in the modern self-service sales system where the way of merchandises are exposed frequently works like a buying list to the clients. For this reason, it has customers that even not having planned the purchase of one specific item decide for buying it once inside the store whereas it has those that having planned what to buy, change the idea when into the store and, at the end, don t buy it. The conclusive result of this work, based on a descriptive methodology survey that included exploring characteristics too is that there are, in fact, a strong influence derived from merchandising techniques in both cases, considering that it was found strong evidences in which a considerable part of these behaviors at least were provoked by factors like the merchandise s physical positioning and presentation in the sales area elements that are firmly linked to the point-of-purchase merchandising efforts. As a result, and depending on the manner these techniques could be correctly, wrongly or not applied, the merchandising action in supermarkets can really influence the pre-planned consumer s purchases in a such intense way that they may effectively change its plans even during the act of purchases either considering to buy something that had not been foreseen to buy, either in given up for buying something that effectively was in their purchasing plan. So, it is confirmed herein that merchandising efforts carried out through retailers and manufacturers in the self-service can really induce the consumer to decide for a purchase, even if that had not been beforehand planned. In the same way, it was also established as certain that the lack of merchandising efforts can lead to a diametrical opposing effect, when the consumer may change his or her mind in buying something he or she had planned to buy before.